The Book of Psalms as the archetext of F. G. Klopshtok’s religious-philosophical lyrics - Sinilo, Galina V. (Journal of the Belarusian State University. Philology, 2019)
This paper examines the problem of biblical archetextuality in the poetry of the outstanding German poet and innovator Friedrich Gottlieb Klopstock (1724 –1803). We show that the «axial» archetext (meaning- and text-generating text) of Klopstock’s religious and philosophical lyrics is the biblical Book of Psalms. We demonstrate that the motives and images of the Psalms (primarily philosophical and contemplative, a kind of «panentheistic») are widely used in his odes, hymns and spiritual song. Psalms also serve as architexts (genre patterns) for the German poet. We further demonstrate that the special poetics of «hearts and tears», characterized by increased emotionality, rapid dynamics of feelings, the ability to convey the state of religious ecstasy, are formed by Klopstock in constant dialogue with the Book of Psalms. Visibility in the transmission of spiritual and physical sufferings, as well as joy and enthusiasm, an abundance of exclamations and invocations, crushing verses, inversions, repetitions, pleonasms, parataxis preference for hypotaxis are related to Klopstock’s style and the style of the Psalms. The unequal tonic verse of the Psalms also influences (along with antique meters) the formation of Klopstock’s «free rhythms» (freie Rhythmen) – the historical first form of the vers libre in its anti-syntactic form. It is under the influence of biblical poetry that Klopstock creates an innovative genre – a religiousphilosophical hymn in free rhythms, the most striking example of which is «Festivity of Spring» («Die Frühlingsfeier»). In the genre of a spiritual song, Klopstock is consciously striving for a song style, referring to free trocheical dimensions and relying on the Lutheran song as architext (at the same time, the Book of Psalms remains the «axial» archetext for him). We show that Klopstock creates a special «ecstatic» version of sentimentalism and is one of Germany’s largest religious poets.